2018
DOI: 10.1038/s41439-018-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel TFAP2A mutation in a Japanese family with Branchio-oculo-facial syndrome

Abstract: Branchio-oculo-facial syndrome (BOFS) is a rare autosomal dominant disorder characterized by craniofacial, ocular, and ectodermal anomalies. BOFS is caused by mutation of the transcription factor AP2-alpha gene (TFAP2A). We performed detailed genetic analysis of a Japanese family with clinically suspected BOFS and identified a novel missense mutation resulting in a predicted amino-acid substitution in the highly conserved basic DNA-binding domain of TFAP2A (NM_003220.2:c.699A>C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Like most dominant diseases, BOFS expresses a considerable phenotypic variabilities. The patients displayed variable severity of clinical symptoms, even with the same mutation in the inter-intrafamily due to incomplete penetrance ( 5 , 15 17 ) and somatic mosaicism ( 10 ). Titheradge et al ( 18 ) reported a three generational BOFS family with c.703G >A, p.(Glu235Lys), demonstrating wide phenotypic spectrum, including lethality.…”
Section: Discussionmentioning
confidence: 99%
“…Like most dominant diseases, BOFS expresses a considerable phenotypic variabilities. The patients displayed variable severity of clinical symptoms, even with the same mutation in the inter-intrafamily due to incomplete penetrance ( 5 , 15 17 ) and somatic mosaicism ( 10 ). Titheradge et al ( 18 ) reported a three generational BOFS family with c.703G >A, p.(Glu235Lys), demonstrating wide phenotypic spectrum, including lethality.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from the peripheral blood samples of II‐1 and II‐2 in Pedigree 1 (Figure a), and I‐1 and I‐2 in Pedigree 2 (Figure b) using the QIAamp DNA Blood Midi Kit (Qiagen, Venlo, Netherlands) following the manufacturer's instructions, and from umbilical cord samples from III‐1 and III‐2 in Pedigree 1 and chorionic villi samples from II‐2 in Pedigree 2 using conventional phenol/chloroform/isoamyl alcohol extraction (Sato et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…We performed whole‐exome sequencing, alignment, annotation, and data filtering on II‐1, II‐2, and III‐2 in Pedigree 1 as previously described (Sato et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations